2023
DOI: 10.1149/1945-7111/acdd25
|View full text |Cite
|
Sign up to set email alerts
|

Ni/NiO Reference Electrode Potential Measurements in Molten CaCl2–CaO

Olivia R. Dale,
Forest Felling,
Mario Gonzalez
et al.

Abstract: A direct oxide reduction (DOR) process is used to reduce PuO2 to Pu metal via Ca metal. Molten CaCl2 is commonly used as the electrolyte for this reaction. As the DOR reaction proceeds, CaO accumulates in the salt and must be measured in real-time to know when the reaction has gone to completion. Open circuit potential (OCP) was measured in this study between a reference electrode consisting of Ni/NiO contained in an MgO tube and a tungsten working electrode. Two methods of CaO additions were performed over se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…11 For detecting oxide ions in a calcium chloride salt, open circuit potentiometry (OCP) measurements are especially notable, as Dale et al found a correlation between OCP measurements to oxide ion concentrations up to 14.4 wt% and showed that correlation matched the Nernst equation for concentrations up to 5.2 wt%. 13 Alternatively, Zhang et al proposed an in situ real-time electrochemical sensor using three tungsten electrodes to detect oxide ion concentrations in molten salt via cyclic voltammetry (CV). 14 Oxide ions sensing with tungsten and cyclic voltammetry is possible because of an oxidation reaction between the tungsten electrodes and the dissolved CaO and oxide ions solution.…”
mentioning
confidence: 99%
“…11 For detecting oxide ions in a calcium chloride salt, open circuit potentiometry (OCP) measurements are especially notable, as Dale et al found a correlation between OCP measurements to oxide ion concentrations up to 14.4 wt% and showed that correlation matched the Nernst equation for concentrations up to 5.2 wt%. 13 Alternatively, Zhang et al proposed an in situ real-time electrochemical sensor using three tungsten electrodes to detect oxide ion concentrations in molten salt via cyclic voltammetry (CV). 14 Oxide ions sensing with tungsten and cyclic voltammetry is possible because of an oxidation reaction between the tungsten electrodes and the dissolved CaO and oxide ions solution.…”
mentioning
confidence: 99%